Cycling facilities: designing for safety. - (:unkn) unknown (Deutsches Institut für Urbanistik (Difu), 2013)
The German cycling design standards offer a wide spectrum of design concepts to provide safe cycle facilities for a variety of different situations. The main features of safe cycle infrastructure are primarily based on good intervisibility between motor-vehicle drivers and cyclists. The quality of the design of the individual cycle facility is important. The design must allow for an intuitive understanding of the facilities and the corresponding, desired behaviour. Given the increases in cycle traffic, cycling facilities introduced today should also be able to meet future demand, making costly investments at a later stage unnecessary. (Difu)
Keywords: Fahrradinfrastruktur; Radverkehrsanlage; Radverkehrssicherheit; Handlungsempfehlung; Radverkehrsplanung; Schutzstreifen; Sichtbarkeit; ERA 2010; Individualverkehr; Fahrradverkehr; Verkehrsplanung; Verkehrssicherheit